1997
DOI: 10.1161/01.cir.95.7.1844
|View full text |Cite
|
Sign up to set email alerts
|

Bridge Experience With Long-term Implantable Left Ventricular Assist Devices

Abstract: Over all, our medium-term experience with implantable LVAD support is encouraging. Although additional areas of investigation exist, improvements in patients selection and management together with device alterations that have reduced the thromboembolic incidence and facilitated patient rehabilitation lead us to believe that a prospective, randomized trial is indicated to study the role that LVADs may have as an alternative to medical management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
83
0
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(88 citation statements)
references
References 20 publications
1
83
0
4
Order By: Relevance
“…Indeed, a small subgroup of patients can be successfully weaned from LVAD after recovery of ventricular function. 6,[11][12][13][14] Although it has been suggested that these beneficial changes are attributed to chronic unloading of the ventricular myocardium, the molecular mechanisms that play a role in LVAD-induced myocardial plasticity and LV remodeling remain undefined. …”
mentioning
confidence: 99%
“…Indeed, a small subgroup of patients can be successfully weaned from LVAD after recovery of ventricular function. 6,[11][12][13][14] Although it has been suggested that these beneficial changes are attributed to chronic unloading of the ventricular myocardium, the molecular mechanisms that play a role in LVAD-induced myocardial plasticity and LV remodeling remain undefined. …”
mentioning
confidence: 99%
“…13,14 The LVAD used in the present study obtains oxygenated blood from the native left ventricle and sends it to the arterial circulation. Thus, patients are dependent on the output of the prosthetic heart, which is tightly regulated by the programming mode, for maintenance of blood pressure.…”
mentioning
confidence: 99%
“…Endocarditis in patients with LVAD has a 50% mortality rate (7). LVAD-associated endocarditis is defined as clinical evidence of pump and/or cannula infection along with the presence of vegetation on echocardiography or a vascular phenomenon as defined by modified Duke's criteria (15).…”
Section: Endocarditis In Lvadmentioning
confidence: 99%
“…But it's strongly emphasized that eradication of fungemia with drugs alone without LVAD removal is an impossible task (15). In summary, the effective treatment methodologies for positive outcomes in patients with LVAD endocarditis were documented to be treating a patient with systemic antibiotic suppression therapy alone, LVAD replacement, LVAD transplantation and LVAD explantation without transplantation (7). More clinical data is required for a specific treatment approach for LVAD endocarditis regarding the use of just antibiotics versus device exchange and explantation.…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation